Прочность паяных сочленений нитридокремниевой керамики со сталью и влияние мартенситного превращения и аномалий механических свойств стали - Найдич, Ю.В.; Мильман, Ю.В.; Костюк, Б.Д.; Москаленко, С.А.; Гончарук, В.А. (Доповіді НАН України, 2010)
Виконано паяння при 900 °С у вакуумi (10^−3 Па) за допомогою титанвмiщуючих припоїв. При тому ж режимi були вимiрянi термiчнi розширення рiзних сталей автоматичним вакуумним дилатометром при 20–900–20 °С. Мiцнiсть на згин з’єднання Si3N4/сталь III (хiмiчний склад сталi: 0,3% С, 3% Cr, 0,4% Mn, 3% Ni, 0,5% Mo) була набагато бiльшою, нiж для iнших сталей. Тiльки в сталi III спостерiгалося iнтенсивне мартенситне перетворення. Виконанi спецiальнi дослiдження механiчних властивостей сталi III при рiзних температурах. Розроблена концепцiя розумiння явища високої мiцностi з’єднання Si3N4/сталь III. Ми впевненi, що причиною цього є спецiальнi умови пружнопластичної деформацiї в контактнiй зонi металевої частини з’єднання, якi викликанi мартенситним перетворенням (ефект псевдопластичностi, явище, подiбне ефекту пам’ятi форми) i дуже високою пластичнiстю сталi в аустенiтнiй фазi до мартенситного перетворення. Цi фактори забезпечують релаксацiї напружень, що призводять до збiльшення мiцностi спаю. The strength of brazed Si3N4/steel joints is investigated when the thermal expansion coefficients (TEC) of materials to be joined are significantly different (TEC = (1.5–2) · 10^−6/°C for Si3N4 ceramics and TEC = 10.5 · 10^−6/°C–13.2 · 10^−6/°C for 3 investigated steels). Brazing process was carried out at 900 °C in vacuum (10^−3 Pa) with the aid of titanium-containing solders. At the same regime, thermoexpansion of various steels was measured by automatic vacuum dilatometer at 20–900–20 °C. The bend strength for the joint Si3N4/steel III (chemical composition of steel III is 0.3% C, 3% Cr, 0.4% Mn, 3% Ni, 0.5% Mo) was much more than that for other steels. Only in this steel, the intensive martensitic transformation was observed. Special investigations of mechanical properties of steel III are carried out at various temperatures. The reason for the phenomenon of high strength of the joint Si3N4/steel III is the special stress-strain-deformability conditions in the contact zone of the metal part of the joint, caused by the martensitic transformation (effect of pseudoelasticity like the effect of form memory) and very high plasticity of the steel in the austenitic phase before the martensitic transformation. These factors promote the strain relaxation and increase the joint strength strongly.